ANALISIS KEUANGAN BPRS AL-SALAAM AMAL SALMAN DENGAN MODEL SHARIA CONFORMITY AND PROFITABILITY (SCnP) DAN TEKNIK DUPONT SYSTEM - Risna Nur Azizah; Arief Widyananto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This study aims to explain the Islamic financial performance based on the DuPont System Technique and Sharia conformity and Profitability (SCnP) at the Al-Salaam Amal Salman BPRS for the 2016-2020 period by analyzing two variables, namely sharia conformity or sharia conformity and profitability. This study uses quantitative research. Data retrieval in the form of secondary data obtained indirectly from information or additional data used in the form of journals, websites, and other data related to research. The method used is SCnP with sharia conformity ratios namely Sharia Investment, Sharia Income and Profit Sharing Ratios Return On Assets (ROA), Return On Equity (ROE) and Profit Margin Ratio while the DuPont System method uses the ratio of Net Profit Margin (NPM), Total Asset Turn Over (TATO) and Return On Investment (ROI). The result of the study is analysis of the financial performance of BPRS Al-Salaam Amal Salman for the 2016-2019 period using Sharia conformity and Profitability is in the Upper Right Quadran (URQ) position which indicates the bank has a high level of compliance with sharia principles and profitability, while in 2020 it is in a position Lower Left Quadrant (LLQ) which indicates the bank has a level of compliance with sharia principles and low profitability. While the analysis using the DuPont System BPRS Al-Salaam Amal Salman has an average Net Profit Margin (NPM) of 23.393%, Total Assets Turn Over (TATO) of 20.666% and Return On Investment (ROI) of 0.029%.